Manajemen Sekolah dalam Meningkatkan Kualitas dan Produktivitas Guru Saiburi Chaengprachakarn School Thailand - Silvia Mimik ati; Erna Resmiatini; Yakaria Awae (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2026)
Teacher quality and productivity are key factors in improving the overall quality of education, including in Thailand. This study aims to analyze the condition of teacher quality and productivity at Saiburi Chaengprachakarn School, Pattani Province, and to identify the factors influencing them. A descriptive qualitative method was employed through interviews, observations, and document analysis. The findings reveal that the school consistently develops its teachers through continuous training, seminars, and competency improvement programs such as educational technology mastery and Teaching English to Speakers of Other Languages (TESOL). Teacher quality is reflected in professionalism, pedagogical skills, subject mastery, and classroom management, while productivity is indicated by discipline, consistency in teaching, innovative methods, and participation in professional development. However, challenges remain, particularly in terms of limited technological facilities, administrative workload, and insufficient incentives. The study concludes that improving teacher quality and productivity requires a holistic strategy that includes strengthening competencies, enhancing school management support, and improving teacher welfare. Keywords: teacher quality, teacher productivity, education in Thailand, Saiburi Chaengprachakarn School, teacher professional development